Narrow Dual Band Frequency Selective Surface Design for X-Band Application - Belen, Mehmet A.; Gulseren, Ahmet H.; Gunes, Filiz (IEEE, 2018)
In today's world where communication is very important, studies on communication systems are continuing rapidly to increase the quality of communication. For this reason, in order to be able to develop in important areas such as communication and radar systems, antenna design studies with different characteristics are gaining importance. Especially in the field of microwave several application have been done by using metamarials. In this study, a band stop dual-band frequency selective surface is proposed in the X band frequencies using a single layer interdigital capacitor structure. When the line widths and gaps on the interdigital capacitor structure are changed, a tunable FSS with dual band resonance frequencies at frequencies of 8-10 GHz is proposed. FR4(eps 4.6, h:1.58mm) is used in FSS design. The unit cell size is 22.2 x 16.6 mm.
Keywords: X-Band; Frequency Selective Surface; Metamaterial; Engineering; Telecommunications